Life cycle assessment on biogas production from straw and its sensitivity analysis. (February 2016) - Wang, Qiao-Li; Li, Wei; Gao, Xiang; Li, Su-Jing
Highlights: This study executes a cradle-to-gate LCA study on biogas production from straw. The process has beneficial effect on synthetic environment. The negative impacts of this process on GHG emission are strengthened with time. Use of gas-fired power burning self-produced NG can create a clearer process. More focus shall be on efficient use of electricity and selection of CO2 absorbent. Abstract: This study aims to investigate the synthetically environmental impacts and Global Warming Potentials (GWPs) of straw-based biogas production process via cradle-to-gate life cycle assessment (LCA) technique. Eco-indicator 99 (H) and IPCC 2007 GWP with three time horizons are utilized. The results indicate that the biogas production process shows beneficial effect on synthetic environment and is harmful to GWPs. Its harmful effects on GWPs are strengthened with time. Usage of gas-fired power which burns the self-produced natural gas (NG) can create a more sustainable process. Moreover, sensitivity analysis indicated that total electricity consumption and CO2 absorbents in purification unit have the largest sensitivity to the environment. Hence, more efforts should be made on more efficient use of electricity and wiser selection of CO2 absorbent.